A facile method for the preparation of three-dimensional CNT sponge and a nanoscale engineering design for high performance fiber-shaped asymmetric supercapacitors. Issue 43 (25th October 2017) - Li, Yong; Kang, Zhuo; Yan, Xiaoqin; Cao, Shiyao; Li, Minghua; Liu, Yichong; Liu, Shuo; Sun, Yihui; Zheng, Xin; Zhang, Yue
Abstract : Fiber supercapacitors (FSCs) have great application potential in future smart textiles and portable and wearable electronics because of their flexibility, tiny volume and wearability. Abstract : Fiber supercapacitors (FSCs) have great application potential in future smart textiles and portable and wearable electronics because of their flexibility, tiny volume and wearability. Their main limitation, however, is the low energy density when compared with batteries, which seriously restricts their practical application. How to enhance their energy densities while retaining their high power densities is a critical challenge for fiber-shaped supercapacitor development. Here, we first fabricated three-dimensional CNT sponge (3DCS) by a facile electrochemical activation and freeze-drying method and then synthesized 3DCS/polyaniline nanocomposite fibers by in situ electro-polymerization. Through a rational nanoscale electrode engineering design, the resultant fibers show a specific capacitance as high as 242.9 F cm −1 in 1 M H2 SO4 . Furthermore, a fiber-shaped asymmetric supercapacitor (FASC) was assembled using 3DCS/P as the positive electrode and 3DCS as the negative electrode. After optimization, the FASC delivers a high energy density of 30.92 μW h cm −2, which is about 2 times higher than that of the highest reported previously, and maintains a maximum power density (1.78 mW cm −2 ) more than two orders of magnitude higher than those of micro-batteries and an outstanding mechanical stability with 90.2% specific capacitance retained after 1000 bending cycles. In view of the excellent electrochemical characteristics and the simple manufacturing of the highly conductive and flexible 3DCS/P, it offers new opportunities for designing long-life wearable FSCs with high energy density and high power density.